Governing for Transformative Change across the Biodiversity–Climate–Society Nexus. (1st June 2022) - Pascual, Unai; McElwee, Pamela D; Diamond, Sarah E; Ngo, Hien T; Bai, Xuemei; Cheung, William W L; Lim, Michelle; Steiner, Nadja; Agard, John; Donatti, Camila I; Duarte, Carlos M; Leemans, Rik; et al.
Abstract: Transformative governance is key to addressing the global environmental crisis. We explore how transformative governance of complex biodiversity–climate–society interactions can be achieved, drawing on the first joint report between the Intergovernmental Panel on Climate Change and the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services to reflect on the current opportunities, barriers, and challenges for transformative governance. We identify principles for transformative governance under a biodiversity–climate–society nexus frame using four case studies: forest ecosystems, marine ecosystems, urban environments, and the Arctic. The principles are focused on creating conditions to build multifunctional interventions, integration, and innovation across scales; coalitions of support; equitable approaches; and positive social tipping dynamics. We posit that building on such transformative governance principles is not only possible but essential to effectively keep climate change within the desired 1.5 degrees Celsius global mean temperature increase, halt the ongoing accelerated decline of global biodiversity, and promote human well-being.